2015
DOI: 10.1016/j.yjmcc.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of syndecan-4 promotes immune cell recruitment and mitigates cardiac dysfunction after lipopolysaccharide challenge in mice

Abstract: Inflammation is central to heart failure progression. Innate immune signaling increases expression of the transmembrane proteoglycan syndecan-4 in cardiac myocytes and fibroblasts, followed by shedding of its ectodomain. Circulating shed syndecan-4 is increased in heart failure patients, however the pathophysiological and molecular consequences associated with syndecan-4 shedding remain poorly understood. Here we used lipopolysaccharide (LPS) challenge to investigate the effects of syndecan-4 shedding in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 49 publications
0
57
1
Order By: Relevance
“…Strand et al . reported that the shedding of syndecan‐4 promotes leukocyte recruitment after a lipopolysaccharide challenge in mice.…”
Section: Evaluation Of Glycocalyx Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Strand et al . reported that the shedding of syndecan‐4 promotes leukocyte recruitment after a lipopolysaccharide challenge in mice.…”
Section: Evaluation Of Glycocalyx Damagementioning
confidence: 99%
“…Syndecan-4 is known as a binding site of antithrombin, and its derangement decreases the activity of antithrombin [47]. Strand et al [53] reported that the shedding of syndecan-4 promotes leukocyte recruitment after a lipopolysaccharide challenge in mice.…”
Section: Measurement Of Glycocalyx In Plasma and Urinementioning
confidence: 99%
“…Lumican, also a member of the SLRP family, induces pro-fibrotic signaling through activation of NFκB and is associated with increased cardiac fibrosis and development of heart failure in mice subjected to left ventricular pressure overload [104,105]. Moreover, the shed extracellular domain of the transmembrane proteoglycan syndecan-4 activates NFκB, and affects transcription of collagens and SMA in cultured cardiac fibroblasts [106]. Smaller fragments of the large extracellular carbohydrate chain hyaluronic acid (HA) have also been found to activate TLRs [107,108].…”
Section: Mechanical Activation Of Extracellular Matrix: a Vigilantmentioning
confidence: 99%
“…Cardiac fibroblasts in culture exposed to increased levels of shed syndecan-4 respond with altered expression of ECM genes [106], favoring ECM degradation. Cardiac fibroblasts treated with shed syndecan-4 fragments show reduced collagen I and III expression and reduced proliferation.…”
Section: Cell Surface Mechanotransduction: a Strained Relationshipmentioning
confidence: 99%
“…The endothelial glycocalyx, a layer of negatively charged gel-like substance, exists on surfaces of pulmonary vascular endothelial cells. Heparan sulfate (HS) and syndecan-4 (SDC-4) are highly abundant in the glycocalyx [3,4]. The endothelial glycocalyx plays an important role in albumin exudation formation, leukocyte adhesion, and anticoagulation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%